THE IMPORTANCE OF CONTINUOUS CARE IN PRENATAL: AN ANALYSIS ON RECORDS ON THE PREGNANT WOMAN’S CARD - Quitéria Fernandes Ferreira, Ana; Raulino de Barros, Emille; Cutalo Moreira, Marcela; Gomes da Silva, William; Corrêa Bezerra de Araújo, Renata; Carolina Salustino, Maria; Allyson Gomes Ferreira, Jefferson (Health and Society, 2023)
The Pregnancy Card is the main way of identifying the health status of the pregnant woman and fetus included in prenatal care. With the aim of highlighting and identifying the importance of notes on the elements recorded in the pregnant woman’s book during prenatal care based on the analysis of published articles and their relevance in prenatal care, delivery and puerperium, in the case of a review systematic. The research was obtained through the analysis of articles published according to inclusion and exclusion criteria, resulting in a set of 10 articles showing dissatisfaction with the number of current records presented in virtual bases, where a need for practical investigative increase on the use of the pregnant woman’s card and the importance it has for its purpose.